(3CQLhRI aj GdHdGZIs - (3GdMehj , CMeO Hf eMeO ecj, TgGH GdOjf CHh GdYHGS,J (B1098 (3g` s
(3ChdgG (B:s
(3hHYO UZjQI GdMLe eY GdEjLGQ , YOjeI GdfXjQ ddEYLGR s
(3BNQgG (B:s
(3hefYg HYOe GdJQcjH , ef GdMQha hGYJeOg HJfLH s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3CdagG SfI (B1075s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B93s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3HdGZI (B471) s
Keywords: (3GdHdGZIs